OUTBREAK OF SALMONELLA FOOD POISONING AT HIGH ALTITUDE - SINGH, MANDEEP (Med J Armed Forces India, 1998)
An outbreak of food poisoning occurred among soldiers of an army unit located at high altitude (3300m) in western Himalayas. A total of 78 of the 103 soldiers who had consumed the incriminated meal suffered from the illness. Sixteen of the 78 had symptoms severe enough to warrant admission to hospital. The symptoms consisted of diarrhoea, vomiting, fever, headache, vertigo and abdominal cramps of varying intensity. Salmonella enteritidis was isolated from 6 stool samples and in one blood sample. Epidemiologically, frozen fowl was traced as the probable incriminating food agent responsible for the outbreak. This is probably the first such outbreak being reported from high altitude. It is of significance for the Indian Armed Forces, as the cause of the food poisoning was traced to an inherent shortcoming in the supply of food items to the troops located in far flung and isolated regions and in the cooking practices being followed.